Host and Bacterial Iron Homeostasis, an Underexplored Area in Tuberculosis Biomarker Research - Baatjies, Lucinda; Loxton, Andre G.; Williams, Monique J. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (Mtb) a human adapted pathogen has found multiple ways to manipulate the host immune response during infection. The human immune response to Mtb infection is a highly complex cascade of reactions, with macrophages as preferred intracellular location. Interaction with the host through infection gives rise to expression of specific gene products for survival and multiplication within the host. The signals that the pathogens encounter during infection cause them to selectively express genes in response to signals. One strategy to identify Mtb antigens with diagnostic potential is to identify genes that are specifically induced during infection or in specific disease stages. The shortcomings of current immunodiagnostics include the failure to detect progression from latent infection to active tuberculosis disease, and the inability to monitor treatment efficacy. This highlights the need for new tuberculosis biomarkers. These biomarkers should be highly sensitive and specific diagnosing TB infection, specifically distinguishing between latent infection and active disease. The regulation of iron levels by the host plays a crucial role in the susceptibility and outcome of Mtb infection. Of interest are the siderophore biosynthetic genes, encoded by the mbt-1 and mbt-2 loci and the SUF (mobilization of sulphur) operon (sufR-sufB-sufD-sufC-csd-nifU-sufT), which encodes the primary iron-sulphur cluster biogenesis system. These genes are induced during iron limitation and intracellular growth of Mtb, pointing to their importance during infection.